Routing algorithm for supporting data-differentiated service in hybrid wireless mesh networks in underground mines - Haifeng Jiang; Liansheng Lu; Guangzhi Han; He Wang; Shanshan Ma; Renke Sun (International Journal of Distributed Sensor Networks)
Hybrid wireless mesh networks are more suitable to tunnels in underground mines because mesh clients can perform the routing functionality and provide end-user applications. Types of data transmitted among hybrid wireless mesh networks in underground mines are diverse and power supply of clients is limited. Using virtual potential field, a routing algorithm is proposed to support data-differentiated service in hybrid wireless mesh networks. Based on network parameters, the hybrid wireless mesh networks are abstracted as potential fields. The hop count is used to build the depth potential field. The residual energy of nodes is converted into penalty factor to symbolize the used buffer spaces of nodes, which is used to construct resource potential field to support different types of data. According to the different demands of data transmission, the proportion of these two potential fields is adjusted by a regulatory factor to form a hybrid potential field. The data packets are driven to move toward the gateway in the hybrid potential field at the same time to achieve high quality of service. Simulation results demonstrate that the proposed routing algorithm has shown better performance on end-to-end delay, delivery ratio, and network lifetime, compared with similar algorithms.